Energetics of bacterial growth: balance of anabolic and catabolic reactions. - Russell, J B (1995)
Biomass formation represents one of the most basic aspects of bacterial metabolism. While there is an abundance of information concerning individual reactions that result in cell duplication, there has been surprisingly little information on the bioenergetics of growth. For many years, it was assumed that biomass production (anabolism) was proportional to the amount of ATP which could be derived from energy-yielding pathways (catabolism), but later work showed that the ATP yield (YATP) was not necessarily a constant. Continuous-culture experiments indicated that bacteria utilized ATP for metabolic reactions that were not directly related to growth (maintenance functions). Mathematical derivations showed that maintenance energy appeared to be a growth rate-independent function of the cell mass and time. Later work, however, showed that maintenance energy alone could not account for all the variations in yield. Because only some of the discrepancy could be explained by the secretion of metabolites (overflow metabolism) or the diversion of catabolism to metabolic pathways which produced less ATP, it appeared that energy-excess cultures had mechanisms of spilling energy. Bacteria have the potential to spill excess ATP in futile enzyme cycles, but there has been little proof that such cycles are significant. Recent work indicated that bacteria can also use futile cycles of potassium, ammonia, and protons through the cell membrane to dissipate ATP either directly or indirectly. The utility of energy spilling in bacteria has been a curiosity. The deprivation of energy from potential competitors is at best a teleological explanation that cannot be easily supported by standard theories of natural selection. The priming of intracellular intermediates for future growth or protection of cells from potentially toxic end products (e.g., methylglyoxal) seems a more plausible explanation.